RELASI KUASA DALAM PRAKTIK SUKUR BUMI - Heriyawati, Yanti (Jurnal Kawistara, 2012)
This writing is a study on the form of power relations in Sukur Bumi as a cultural practice. Sukur Bumi is a sacred ritual activity conducted by the people in Rancakalong as a gratitude of their harvest. Power is not only meant as authority and hegemony, but also as symbolic power. The power has its power to construct knowledge and truth. The power relation is in three level, that is, between the society and Sukur Bumi, the government and the society, and between the society, Sukur Bumi, and the government. In the end, Sukur Bumi has its own power. Its meaning and symbols has the power to control the society and the government. Without Sukur Bumi, both the government and the society do not have their sphere to construct the power.